Effect of Statins for Primary Prevention of Cardiovascular Disease According to the Fatty Liver Index - Joonsang Yoo; Jimin Jeon; Minyoul Baik; Jinkwon Kim (Springer, 2024)
Abstract Introduction Nonalcoholic fatty liver disease (NAFLD) is associated with increased risk of cardiovascular disease (CVD). We investigated the primary preventive effect of statins on CVD according to the level of fatty liver index (FLI), which is a marker of NAFLD. Methods We conducted a nested case-control study on the basis of a nationwide health screening cohort in Korea. The participants were divided into tertiles (T1, T2, and T3) according to their FLI score. Cases were defined as individuals who developed CVD (composite of myocardial infarction and stroke). Three controls were matched to each case and multivariable conditional logistic regression analysis was performed. Results Within a cohort of 206,263 participants without prior CVD, 7044 individuals suffered the primary outcome. For the nested case-control study, we selected these 7044 cases along with their corresponding 20,641 matched controls. Individuals in the T3 tertiles of FLI had a higher risk of CVD than those in the T1 tertile [adjusted odds ratio (OR) 1.30; 95% confidence interval (CI) 1.20-1.40, P < 0.001]. In sub-analyses based on FLI tertiles, statin therapy was associated with a lower risk of CVD (adjusted OR 0.72; 95% CI 0.61-0.85, P < 0.001) in the T3 tertile but not in the T1 and T2 tertiles. Conclusions Statin therapy was associated with a reduced risk of CVD in individuals with high FLI but not in those with low FLI. Further research is needed to determine the pathophysiologic mechanism between statin and NAFLD.